How attempts to meet others' unrealistic expectations affect health: health-promoting behaviours as a mediator between perfectionism and physical health. Issue 3 (2nd April 2016) - Harrison, Fleur; Craddock, Alan E.
Abstract : The traits of perfectionism have been associated with health and longevity. Theoretically and empirically, health behaviours are considered a primary mechanism through which such associations of personality and health occur. However, scant evidence to date indicates behaviours did not mediate between perfectionism and health as anticipated. The aim of the current research was therefore to rigorously examine whether health behaviours mediated associations of perfectionism and physical health-related quality of life (HRQL). A sample of 263 students completed questionnaires measuring subtypes of perfectionism, HRQL, self-efficacy and health-promoting behaviours. Hierarchical regression analyses investigated predictors of physical HRQL and health-promoting behaviours. Non-parametric bootstrapping techniques assessed whether health-promoting behaviours mediated significant associations between perfectionism and physical HRQL. Socially prescribed perfectionism (SPP) significantly predicted poorer physical HRQL, and this association was mediated by health-promoting behaviours, a unique finding. Self-oriented perfectionism did not significantly predict physical HRQL, but was linked with more numerous health-promoting behaviours. In conclusion, results suggest that individuals higher in SPP, who are overly concerned with evaluation by others and with meeting perceived unrealistically high standards of performance, performed fewer health-promoting behaviours, and this mediated the association between SPP and poorer physical HRQL. More broadly, perfectionism predicted physical HRQL and engagement or lack thereof in health-promoting behaviours and should be considered as part of health promotion strategies.